Rupture process of the Mw = 7.9 2015 Gorkha earthquake (Nepal): Insights into Himalayan megathrust segmentation. Issue 20 (24th October 2015) - Grandin, Raphaël; Vallée, Martin; Satriano, Claudio; Lacassin, Robin; Klinger, Yann; Simoes, Martine; Bollinger, Laurent
Abstract: We investigate the rupture process of the 25 April 2015 Gorkha earthquake ( Mw = 7.9) using a kinematic joint inversion of teleseismic waves, strong motion data, high‐rate GPS, static GPS, and synthetic aperture radar (SAR) data. The rupture is found to be simple in terms of coseismic slip and even more in terms of rupture velocity, as both inversion results and a complementing back projection analysis show that the main slip patch broke unilaterally at a steady velocity of 3.1–3.3 km/s. This feature likely contributes to the moderate peak ground acceleration (0.2 g) observed in Kathmandu. The 15 km deep rupture occurs along the base of the coupled portion of the Main Himalayan Thrust and does not break the area ranging from Kathmandu to the front. The limitation in length and width of the rupture cannot be identified in the preearthquake interseismic coupling distribution and is therefore discussed in light of the structural architecture of the megathrust. Key Points: Uniform rupture velocity during peak moment release explains modest acceleration in Kathmandu High‐frequency radiation occurred preferentially along the downdip edge of the high slip patch The MHT is locked updip of the 2015 event, suggesting high level of seismic hazard toward the front